Strategi Kepolisian Resort Kota Besar Medan dan Upaya Masyarakat dalam Pembentukan Kawasan Bersih dari Narkoba (Studi Kasus di Kampung Kubur Kota Medan) - Yuendi Satria Apratama; Intan Fitri Meutia; Dodi Faedlulloh (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2023)
The problem of drug abuse has a negative impact not only on users but also on the surrounding community. The increasingly widespread use of drugs has involved users from various circles, ranging from adults, teenagers and even children. Drug abuse requires special attention from various parties, both the community and the authorities. This is because drug abuse is a behavior that violates the law and can damage the nation's young generation. Kampung Kubur is one of the drug trafficking sites in North Sumatra. The existence of Kampung Kubur presents places such as prisons and mini discotheques which are used as places for prisoners and fun. This research approach is a qualitative research with descriptive type data sources obtained by interview, observation and documentation methods. The results of this study indicate that the police strategy and community efforts have succeeded in establishing a drug-free area.